Airborne wind turbine shell behavior prediction under various wind conditions using strongly coupled fluid structure interaction formulation. (15th July 2016) - Saeed, Muhammad; Kim, Man-Hoe
Highlights: A fully coupled fluid structure interaction analysis was conducted for airborne wind turbine shell. Airborne wind turbine shell was tested under different speeds and wind changing conditions. Realignment time with wind flow directions was calculated for airborne wind turbine. Abstract: High altitude wind harvesting has been acknowledged as one of the green and efficient future prospects for renewable energy. Different techniques have been adopted over the time to exploit the source effectively. Airborne Wind Turbine System is one of those techniques that are however still in its initial stages. In the present study, the behavior of the airborne wind turbine shell is predicted numerically under various wind conditions. A partitioned strongly coupled fluid–structure interaction formulation was employed to anticipate the behavior of the turbine shell at different wind speeds and varying angles of attack. Two commercial solvers for fluid and structural domains were engaged as black box solvers. Fixed point iteration with dynamic under relaxation was employed to couple the solvers. Dynamic and kinematic constraints were satisfied at each time step to ensure strong coupling of the solvers. This study would be helpful to better understand the behavior of airborne wind turbine shell under different conditions of the wind for a stable and proficient design.